(untitled) (Research, Society and Development, 2024)
This article investigates the possible relationship between Alzheimer’s disease (AD) and periodontal disease (PD), two prevalent conditions that predominantly affect the elderly population. The objective was to examine and evaluate the association between these diseases, considering recent epidemiological and clinical studies. The methodology involved a literature review using databases such as PubMed, Scielo, and Cochrane Library, with a scope defined between the years 2013 and 2023. Studies that explored the relationships between AD and PD were included, while multiple or non-aligned studies with the objectives were excluded. The results indicate a strong link between PD and AD, evidenced by the presence of chronic inflammation and sharing of pro-inflammatory mediators in both conditions. Additionally, an association between PD and cognitive decline in patients with AD was observed, suggesting a possible role of oral health in the progression of the neurodegenerative disease. It is concluded that understanding this connection has important implications for clinical practice, highlighting the need for therapeutic and preventive interventions aimed at oral health as an integral part of AD management in elderly populations.